Drought tolerance screening of plum rootstocks based on physiological and biochemical traits - Ines Mihaljević; Marija Viljevac Vuletić; Vesna Tomaš; Dominik Vuković; Zvonimir Zdunić (Plant, Soil and Environment)
Drought-tolerant rootstocks with better performance regarding water deficit is important for sustaining orchard productivity, especially in regions where water availability is unpredictable. By selecting appropriate rootstocks, fruit growers can mitigate the adverse effects of insufficient water on yields. However, the response of specific rootstocks to drought remains unknown. Our study examined the drought tolerance of five plum rootstocks (Wavit, Torinell, Adesoto, Penta, and St. Julien) focusing on their physiological and biochemical responses. To assess their tolerance under drought conditions, we evaluated leaf relative water content (RWC), chlorophyll fluorescence, lipid peroxidation, hydrogen peroxide (H2O2), proline, and phenolic content. The results showed that Torinel exhibited the highest performance index (PIABS), maximum PSII photochemical efficiency (Fv/Fm), RWC, lowest lipid peroxidation and H2O2 during the drought-stress condition. Based on our results, we identified Torinel as a rootstock with a great ability to withstand drought, suggesting that it could be applied in the breeding program to increase plum resistance to drought. The study provides insights into the drought tolerance of different plum rootstocks, identifying which ones are better suited for cultivation in water-limited environments.